Shaping of the intra-municipal relations in the contemporary local government on the city of Poznan example = Kształtowanie relacji wewnątrzgminnych we współczesnym samorządzie terytorialnym na przykładzie miasta Poznania - Bartkowiak, Piotr; Krzakiewicz, Marianna (Zielona Góra: Faculty of Economics and Management Press)
The main objective of this article is to evaluate the significance of forming the intra-municipal relations in relation to place marketing, based on the example of the Polish city of Poznan. Different conceptions of place marketing, and intra-municipal relations are defined, their mutual correlation aimed towards increasing a city's value is explained, and intra-municipal relations are illustrated. Poznan was chosen due to the preparatory cooperation which took place between the city, and its citizens.
Keywords: relacje; samorząd terytorialny; marketing terytorialny; poziom życia mieszkańców; relations; territorial self-government; territorial marketing; living standards of residents